Colonialism and Climate Crisis: The Root of Environmental Changes and the Rise of Environmental Awareness in Indonesia - Devi Itawan (IHiS (Indonesian Historical Studies), 2022)
This article explores the roots of environmental changes in the history of the Dutch colonization of Indonesia. It analyzed how the Dutch colonial exploitation, which was based on trade capitalism and later industrial capitalism, drove the re-organization of nature and integrated it into the world market system. As a result, it brought about systematic and structural deforestation, transforming the landscape of many parts of Indonesia. However, the state of deforestation raised concerns about environmental degradation as it is entangled with the importance of sustainability in extracting natural resources. From that point, the colonial environmental awareness paradigm was embarking. This article shows how the Dutch colonization and exploitation system directly led to significant environmental changes accumulated in the current climate crisis. Nevertheless, on the other hand, it also drove environmental awareness.